A STUDY IN VULCANIZATION OF NEOPRENE RUBBER (WRT) BY POLYMETHYLOL RESIN (RESOL) - Mutar, Mohammed Ali (Al-Nahrain Journal of Science, 2010)
The vulcanization of neoprene (WRT) with different loading of polymethylol resin (Resol) wasinvestigated to understand the role of resol as curing agent. The cure rate fasted when resol wasadded to the rubber compound, and the change in the mechanical properties were significant. Animprovement in mechanical properties were seen with 7.5 phr loading of resol, while an adverseeffect observed only with a high loading at 10 phr and in absence of magnesia and zinc oxide fromrubber compound. Rubber compounds containing different loading of resol show slight decrease intensile strength, elongation, and tear strength values after 5 days at 80 C°, while high increase inhardness and modulus at the same conditions.